Penggunaan Media Pembelajaran Interaktif (Video Interaktif) dan Dampaknya Terhadap Pencapaian Hasil Belajar Matematika di SMA Negeri 2 Torgamba - Dini Ramadhani Nasution; Sakinah Ubudiyah Siregar; Laili Habibah Pasaribu (Jurnal Ragam Pengabdian, 2026)
This study examines the management of interactive video-based learning media and its impact on mathematics learning outcomes at SMA Negeri 2 Torgamba. A quantitative approach with an ex post facto correlational design was employed, involving 32 students selected through purposive sampling. Data were collected using questionnaires, tests, and documentation, then analyzed through descriptive statistics, validity and reliability tests, classical assumption tests, and simple linear regression. The results showed that both the management of interactive video media and mathematics learning outcomes fell into the sufficient category, with total means of 15.47 and 14.25, respectively. Regression analysis revealed an R value of 0.442 and R² of 0.195, indicating that media management explains 19.5% of the variation in learning outcomes. The regression coefficient of 0.452 (p = 0.011) confirms a positive and significant effect. These findings suggest that more systematic management of interactive video media can enhance students' mathematics achievement, implying that teachers should design videos purposefully, align them with learning objectives, encourage student engagement, and conduct ongoing evaluation.